Regulatory T cells: first steps of clinical application in solid organ transplantation. (3rd June 2015) - van der Net, Jeroen B.; Bushell, Andrew; Wood, Kathryn J.; Harden, Paul N.
Summary: Solid organ transplantation is the treatment of choice for patients with end‐stage organ failure. To prevent rejection of the transplanted organ continuous treatment with immunosuppressive medication is needed. Immunosuppression may be harmful to the transplant recipient, increasing the risk of cancer, infections and cardiovascular disease. To improve transplant and patient survival, there is a need for an immune‐modulatory regimen that is not only potent in preventing rejection of the transplanted organ, but has less side effects compared to current immunosuppressive regimens. Increasingly, transplantation research focusses on regulatory T cell (Treg) therapy to achieve this aim, in which Treg are used as a strategy to allow reduction of immunosuppression. Currently, the first clinical trials are underway investigating the safety and feasibility of Treg therapy in renal transplantation. This review gives an overview of the rationale of using Treg therapy in transplantation, previous experience with Treg therapy in humans, and the expected safety, potential efficacy and cost‐effectiveness of Treg therapy in solid organ transplantation.